A Study of Overall Thermal Transfer Value (OTTV) in Healthcare Building in Perak Tengah District. - M, Aqilah; Mohd Sari, Kamarul Aini; Mustafa, Mohd Syafiq Syazwan (Progress in Engineering Application and Technology, 2023)
Overall Thermal Transfer Value (OTTV) is a design parameter that indicates the solar thermal load transmitted through the building envelope excluding the roof. Temperature readings were taken for both research healthcare to prove that the internal temperature of the building is still not cool enough even though air conditioning has been installed. Thus, this study was carried out to identify and calculate the Overall Thermal Transfer Value (OTTV) in Klinik Desa Kota Setia (KDKS) and Klinik Kesihatan Ulu Dedap (KSUD) starting in July until September 2022 the value of the OTTV was recorded, and the data intended to analyze based on Malaysian Standard 1525:2019. Accordingly, the data collection methods through site visits, interviews, and measurement of each parameter before implementing into the formula of OTTV. The measurements were used in a 4-in-1 Meter Kit for an environmental parameter for 5 weeks from July to September. The study finds out 7 parameters calculated such as wall area, solar absorption factor, window-to-wall ratio, wall construction U-value, orientation value, glass shading coefficient, and device shading coefficient. Then, the OTTV result for KDKS and KSUD was 72.04 W/m2 and 39.7 W/m2, respectively. For improvement 3 consideration factors, the selection of building materials, the use of shading components, and the installation of thermal insulation play a very important role in achieving good thermal and energy use of air conditioners as well as energy efficiency can be applied to KDKS healthcare.